Do immigrants improve the health of native workers? - Osea Giuntella (IZA World of Labor, 2020)
Public debate on immigration focuses on its effects on wages and employment, yet the discussion typically fails to consider the effects of immigration on working conditions that affect workers' health. There is growing evidence that immigrants are more likely than natives to work in risky jobs. Recent studies show that as immigration rises, native workers are able to work in less demanding jobs. Such market adjustments lead to a reduction in native occupational risk and thus an improvement in native health.
Keywords: I12; J24; J61; 330; immigration; occupational choice; job quality; health